DROUGHT TOLERANCE OF LOCAL ROTE AND CHECK VARIETIES OF GROUNDNUT (Arachis hypogaea L.) UNDER DRY SEASON IN TWO LOCATIONS IN EAST NUSA TENGGARA - Yosep S. Mau; A.S.S. Ndiwa; I G.B.A. Arsa (AGRIVITA Journal of Agricultural Science, 2014)
Groundnut is the most important pulse crop in East Nusa Tenggara (ENT); however, the crop yield in ENT is low due to erratic climatic condition, drought stress, and low yielding ability of most cultivated genotypes. Local Rote is a well-known local groundnut variety in ENT, which is a potential superior variety and parental source due its large seed size and high yielding ability. Information on its resistance to abiotic and biotic stresses is important for its future development. Five groundnut genotypes, Local Rote and check varieties were elucidated to identify drought resistant genotypes. The study was carried out in a split-plot design with three replicates in two locations during dry season 2013. Two irrigation regimes (optimum and stress conditions) were assigned as main plot and 5 groundnut geno-types as sub-plot. Research results revealed significant effect of irrigation by genotype interaction on observed yield and yield compo-nent characters in both locations. Seed yields of most tested genotypes were below their yield potential. Local Rote yielded best over two locations (1.26 t.ha-1 seed yield). Yields of check varieties were below 1.0 t.ha-1. Local Rote was considered tolerant to drought based on STI, GMP, SSI and YL selection indices.Keywords: groundnut, local, variety, drought, tolerance